(untitled) (Revista Contexto & Saúde, 2022)
ABSTRACT Breast cancer incidence increases with age, and its treatment usually has side effects such as joint pain, depression and fatigue. Insufficient physical activity can decrease muscle strength, increase fatigue and reduce quality of life. Given the above, the purpose of this systematic review was to identify the main intervention strategies based on physical activities for women during breast cancer treatment. This study considered four databases: PubMed, SportDiscus, Lilacs, and Scielo, taking into consideration studies of the last five years. The descriptors for physical activity variable were “exercise", “physical activity”, and “motor activity”. For breast cancer variable, the descriptors were “breast neoplasm”, and for participants: “women” and “adults”. Seven studies related to the benefits of physical activity were found, one of those was carried out in Brazil. The variables studied were fatigue, anthropometry, physical activity level (PAL), pain threshold, sleep quality, life quality (LQ), physical fitness (PF), and cortisol level. The types of intervention strategies were in most part through aerobic exercises, resistance/strength training, hydrotherapy, relaxation, yoga and belly dancing. Although there is no consensus on which physical activity, intensity, and frequency are best for the patients, in general, all patients increased their level of physical activity and quality of life, reduced fatigue, and were not impeded by the treatment or found necessary to interrupt it while performing such physical activities.